Stromal-epithelial cell interactions and alteration of branching morphogenesis in macromastic mammary glands - Zhong, Aimei; Wang, Guohua; Yang, Jie; Xu, Qijun; Yuan, Quan; Yang, Yanqing; Xia, Yun; Guo, Ke; Horch, Raymund E.; Sun, Jiaming (Journal of Cellular and Molecular Medicine, 2014)
True macromastia is a rare but disabling condition characterized by massive breast growth. The aetiology and pathogenic mechanisms for this disorder remain largely unexplored because of the lack of in vivo or in vitro models. Previous studies suggested that regulation of epithelial cell growth and development by oestrogen was dependent on paracrine growth factors from the stroma. In this study, a co-culture model containing epithelial and stromal cells was used to investigate the interactions of these cells in macromastia. Epithelial cell proliferation and branching morphogenesis were measured to assess the effect of macromastic stromal cells on epithelial cells. We analysed the cytokines secreted by stromal cells and identified molecules that were critical for effects on epithelial cells. Our results indicated a significant increase in cell proliferation and branching morphogenesis of macromastic and non-macromastic epithelial cells when co-cultured with macromastic stromal cells or in conditioned medium from macromastic stromal cells. Hepatocyte growth factor (HGF) is a key factor in epithelial-stromal interactions of macromastia-derived cell cultures. Blockade of HGF with neutralizing antibodies dramatically attenuated epithelial cell proliferation in conditioned medium from macromastic stromal cells. The epithelial-stromal cell co-culture model demonstrated reliability for studying interactions of mammary stromal and epithelial cells in macromastia. In this model, HGF secreted by macromastic stromal cells was found to play an important role in modifying the behaviour of co-cultured epithelial cells. This model allows further studies to investigate basic cellular and molecular mechanisms in tissue from patients with true breast hypertrophy.
EVALuna2:15560